Addressing Vaccine Hesitancy : Survey and Experimental Evidence from Papua New Guinea - Hoy, Christopher; Wood, Terence; Moscoe, Ellen (World Bank, Washington, DC, 2021)
This paper examines the drivers of COVID-19 vaccine hesitancy and tests various means of increasing people’s willingness to receive a COVID-19 vaccine. The study draws on data collected through a broadly representative phone survey with 2,533 respondents and an online randomized survey experiment with 2,392 participants in Papua New Guinea. Both surveys show that less than 20 percent of the respondents who were aware a vaccine existed were willing to be vaccinated. The main reason respondents stated for their hesitancy regarding the vaccine was concern about side effects; however, the majority also said health workers could change their mind, particularly if information was communicated in person. The phone survey illustrated that people’s level of trust in the vaccine and their beliefs about the behavior of others are strongly associated with their intention to get a COVID-19 vaccine. In contrast, people’s concern about COVID-19, most trusted source of information (including social media), and vaccination history were unrelated to their intention to get vaccinated. The online experiment showed that a message that emphasized the relative safety of the vaccine by highlighting that severe side effects are rare, while also emphasizing the dangers of COVID-19, increased intention to get vaccinated by around 50 percent. Collectively, these results suggest that policy makers would be well placed to direct their efforts to boosting the general population’s trust that getting vaccinated substantially reduces the risk of severe illness or death from COVID-19.